Model desain taman ramah anjing Pomeranian - Cendana, Krisna Dinata; Kohdrata, Naniek; Sugianthara, Anak Agung Gede (Jurnal Arsitektur Lansekap, 2018)
Pomeranian-friendly park design. Pomeranian is one of the small dog breeds that has an attractive appearance and characteristics. Pomeranian dog lovers population in Bali has been growing rapidly since 2008 until 2017. It is recorded that the number of pomeranian breeders is 1.246 of 2.370 breeders (Perkin Bali, 2017). Pomeranian-friendly park design is created as, resting and activities area for dogs within a garden setting. It also can function as a training, socializing and playing place for pomeranian. purpose of study is to utilize the park as a supporter of pomeranian activities that affect physical and mental growth. The design of this park includes elevation, and selection of softscape hardscape materials, design of prototype objects so as to support the security and comfort of pomeranian. The research method using qualitative method of observation, interviewing and literature based. The concept of this design providing pomeranian activity space such as playing space, shade space, rest area, training area, gromming area, also put into consideration the comfort of dog owners as a park user as well as guests who visit with a space planning called cozy area where in that area park users can discuss while relaxing enjoy the view of the garden from the top floor which is the best angle when viewing the garden atmosphere which has iconic landmarks in the form of pavilion-shaped icon pomeranian and a variety of plants that have accents and contrast effects as a visual pleasure.